2018
DOI: 10.24875/gmm.18003614
|View full text |Cite
|
Sign up to set email alerts
|

Pronóstico de pacientes con lupus eritematoso generalizado en una unidad de cuidados intensivos

Abstract: La identificación de factores de riesgo para mortalidad ha permitido mejorar el tratamiento de los pacientes críticos con lupus eritematosos generalizado. Objetivo: Describir las características clínicas y los pronósticos de pacientes graves con lupus eritematosos generalizado ingresados en una unidad de cuidados intensivos. Método: Estudio de cohorte, observacional y descriptivo. Se incluyeron 207 pacientes con lupus eritematosos generalizado enero de 2011 y enero de 2016. Resultados: Durante el periodo del e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The leading cause of admission was activity; this differs from several series, where infection plays a preponderant role [1,21,23]. Only a few cohorts report disease activity as a cause of hospitalization [25,26] and in some, as in the study by Whitelaw et al [27] more than half of the patients had less than six months of diagnosis of SLE, which would explain the predominance of activity. In the present cohort, the average time of diagnosis was two years; the high activity was possibly a reflection of difficulties in outpatient management.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The leading cause of admission was activity; this differs from several series, where infection plays a preponderant role [1,21,23]. Only a few cohorts report disease activity as a cause of hospitalization [25,26] and in some, as in the study by Whitelaw et al [27] more than half of the patients had less than six months of diagnosis of SLE, which would explain the predominance of activity. In the present cohort, the average time of diagnosis was two years; the high activity was possibly a reflection of difficulties in outpatient management.…”
Section: Discussionmentioning
confidence: 77%
“…Re-admissions to ICU 7/45 (21,2) Death 4/33 (12,1) Boldface is the values with stadistic signficance p < 0.05 compared to other series of both rheumatologic diseases in general [2,8,20] as well as those that consider SLE only [1,4,16,[21][22][23][24]. This aspect is important given that mortality in this study is one of the lowest reported even though the SLEDAI score was elevated whether it is compared with the oldest series (40%) [1,16,24] or with the most recent ones, where mortality is around 20% [23,25]. A possible explanation for this finding is the low APACHE score of these patients reflecting an early admission strategy to the ICU.…”
Section: Discussionmentioning
confidence: 81%
“…Overall, these 35 studies comprise a total of 8158 patients. 8, 1418, 20, 21, 23, 25, 26, 2952 The largest cohort was retrieved from a public database, including 34,991 admissions of patients with SLE admitted to the ICU. 52…”
Section: Resultsmentioning
confidence: 99%
“…described that the SOFA score was a factor related to mortality at 28 days in patients with SLE who required intensive care ( p < 0.001). 47…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Hou et al in the univariate analysis the use of immunosuppressive agents was a risk factor for hospitalization, 17 other studies have reported similar results. [18][19][20][21][22] None of the patients had fungal infections, and unfortunately, we didn't perform any detection panel for viral infection, this might represent a bias due to some patients hospitalized due to bacterial infection might had also a concomitant viral infection.…”
Section: Discussionmentioning
confidence: 99%